Volume 1A: General 1980
DOI: 10.1115/80-gt-70
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Character Effects on J79 and F101 Engine Combustor Emissions

Abstract: Results of a program to determine the effects of fuel properties on the pollutant emissions of two US Air Force aircraft gas turbine engines are presented. Thirteen test fuels, including baseline JP-4 and JP-8, were evaluated in a cannular (J79) and a full annular (F101) combustor. The principal fuel variables were hydrogen content, aromatic structure, volatility, and distillation end point. Data analysis shows that fuel hydrogen content is a key fuel property, particularly with respect to high power emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Data for other equivalence ratios showed very similar behaviour. Similar effects of boiling characteristics of the fuels have been noted elsewhere [37,38,39] by Gleason et al on the J-79 and F-101 engines. The work recorded here on the transparent combustor (droplet size near uniform) suggests that Tav has a considerable effect upon the combustion efficiency of a wide range of fuels.…”
Section: /3 Combustor -Wide Range Of Fuels -Atmospheric Conditionssupporting
confidence: 81%
“…Data for other equivalence ratios showed very similar behaviour. Similar effects of boiling characteristics of the fuels have been noted elsewhere [37,38,39] by Gleason et al on the J-79 and F-101 engines. The work recorded here on the transparent combustor (droplet size near uniform) suggests that Tav has a considerable effect upon the combustion efficiency of a wide range of fuels.…”
Section: /3 Combustor -Wide Range Of Fuels -Atmospheric Conditionssupporting
confidence: 81%
“…Similarly, the attempt to apply other correlations to our data met with no success due to incomplete information. However, in order to achieve at least an approximate comparison, Eqn (2) was applied, using an assumed air distribution, to a set of data for a J-79 taken from [9]. Figure 10 shows the result of the predictions, together with some predictions reported in [19] for the same engine.…”
Section: Efficiencymentioning
confidence: 99%
“…Allison has found that aromatic content is important to both in the TF41 [2]. But GE reported that J79 and F101 characteristics correlated best with fuel hydrogen content [1,3]. They found aromatic content to be relatively unimportant.…”
Section: Liner Lifementioning
confidence: 99%